2020
DOI: 10.1093/ofid/ofaa156
|View full text |Cite
|
Sign up to set email alerts
|

Chagas Disease in the New York City Metropolitan Area

Abstract: Background Chagas disease, caused by the parasite Trypanosoma cruzi, once considered a disease confined to Mexico, Central America, and South America, is now an emerging global public health problem. An estimated 300 000 immigrants in the United States are chronically infected with T. cruzi. However, awareness of Chagas disease among the medical community in the United States is poor. Methods We review our experience managing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Studies on the clinical epidemiological profile of patients with chronic CD in urban centers reported that the mean age showed the same increasing trend in the last decades, ranging from 37.7 to 67.5 years 12 , 13 , 15 , 20 - 22 . Studies conducted in nonendemic regions of the Northern Hemisphere, where patients migrated from South America, especially Bolivia and Central America, reported younger patients with chronic CD with a mean age ranging from 28.5 to 47 years 16 - 18 , 34 - 37 , reflecting the lack of CD vectorial transmission control in their countries of origin and that CD vectorial transmission remained active in rural areas. The present study showed a progressive increase over time in the age of patients who were included in the study cohort during the 5-year intervals of the study period, with the mean age increasing from 44.3 to 57.1 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the clinical epidemiological profile of patients with chronic CD in urban centers reported that the mean age showed the same increasing trend in the last decades, ranging from 37.7 to 67.5 years 12 , 13 , 15 , 20 - 22 . Studies conducted in nonendemic regions of the Northern Hemisphere, where patients migrated from South America, especially Bolivia and Central America, reported younger patients with chronic CD with a mean age ranging from 28.5 to 47 years 16 - 18 , 34 - 37 , reflecting the lack of CD vectorial transmission control in their countries of origin and that CD vectorial transmission remained active in rural areas. The present study showed a progressive increase over time in the age of patients who were included in the study cohort during the 5-year intervals of the study period, with the mean age increasing from 44.3 to 57.1 years.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the clinical form of CD conducted in urban areas have shown that the cardiac form predominates, with a prevalence ranging from 56% to 66% 12 - 16 , 22 , 23 Few studies have reported a higher incidence of the indeterminate form, varying between 56% and 81.6% 17 , 20 . These differences in the prevalence of clinical forms are attributed to the profile of the healthcare unit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long experience with Chagas disease patients in countries in Latin America and other continents [ 1 , 2 ] shows no evidence that they have more pulmonary infections than the population in general. However, cases with esophageal dilation and content retention are exposed to aspiration of such esophageal content, which may happen after esophageal-pharyngeal reflux [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chagas disease, a consequence of infection with flagellate protozoan Trypanosoma cruzi, affects mainly the heart and digestive system [1][2][3][4][5]. The whole digestive system has its function impaired to some degree [4,5], whereas the changes caused by the disease in the esophagus and colon have clinical importance, as they can result in megaesophagus and megacolon, leading to dysphagia and constipation [2,4,5].…”
Section: Introductionmentioning
confidence: 99%